JMJD1A/NR4A1 Signaling Regulates the Procession of Renal Tubular Epithelial Interstitial Fibrosis Induced by AGEs in HK-2 - Wang, Shaoting; Zuo, Anna; Jiang, Weiqiang; Xie, Jiarun; Lin, Haoyu; Sun, Wei; Zhao, Min; Xia, Jinjin; Shao, Junqiao; Zhao, Xiaoshan; Liang, Donghui; Yang, Aicheng; et al. (Frontiers in Medicine, 2022)
Diabetic kidney disease (DKD) is one of the most serious complications of diabetic patients. Advanced glycation end products (AGEs) induce epithelial-mesenchymal transformation (EMT) of renal tubular epithelial cells (HK-2), resulting in renal tubulointerstitial fibrosis. However, the underlying epigenetic mechanisms remain to be further investigated. In this work, we investigated the functional role of JMJD1A involved in DKD progression. The molecular mechanism study was performed in AGEs-induced HK-2 cells by gene expression analysis, RNA sequencing (RNA-seq), and JMJD1A lentiviral knockdown and overexpression particle transfection. The results showed that AGEs could upregulate JMJD1A, and the expressions of related fibrotic factor were also increased. At the same time, in the DKD animal model induced by unilateral nephrectomy plus streptozotocin (STZ), IHC immunohistochemical staining showed that compared with the control group, the expressions of JMJD1A, FN, and COL1 in the model group were all increased, masson staining results also show that the model group has typical fibrotic changes. This is consistent with the results of our in vitro experiments. In order to determine the downstream pathway, we screened out JMJD1A downstream transcription factors by RNA-seq. Further analysis showed that JMJD1A overexpression could accelerate the progression of AGEs-induced renal fibrosis by reducing the expression of NR4A1 in HK-2 cells. Meanwhile, NR4A1 inhibitor can promote the expression of fibrosis-related factors such as VIM, a-SMA in HK-2 cells, and aggravate the process of fibrosis. Taken together, JMJD1A/NR4A1 signaling can regulate the procession of renal tubular epithelial interstitial fibrosis induced by AGEs in HK-2.